Financial Technology Adoption on Payment Systems and Financial Transactions Among Millenials in Indonesia - Adiyaksa Pratama; Anas, Eka Pria (Syntax Corporation, 2024)
This research aims to see how far the adoption of digital payment systems and electronic financial transactions in Indonesia is based on the factors used in the theory acceptance model (TAM) method, such as perceived usefulness and perceived ease of use. Several factors, such as social influences, financial literacy, security and privacy, and government support, are added to the effects of the intention to adopt digital payments, especially after the COVID-19 pandemic. Data processes with SmartPLS 3 and uses SEM-PLS method to see that all the factors are supported to adopt digital payment systems in Indonesia. Results show that perceived usefulness and ease of use are the factors that drive the intention to adopt digital payment systems. Besides that, government support drives the intention to adopt digital payment systems by regulations to develop digital payment ecosystems. Others such as social influences, financial literacy, and security-privacy aren’t influenced on intention to adopt digital payment systems in Indonesia.